Strategic thinking among Malay And Chinese Entrepreneurs in Malaysia - Syed Azizi Wafa Syed Khalid Wafa; Ramraini Ali Hassan; Mat Salleh Ayub; Siti Hajar Mohd Noor (2016)
Previous researches on Malaysian managers and entrepreneurs have shown significant differences in their management styles and practices. This study sought to determine if there are any significant differences in the strategic thinking abilities of Malay and Chinese entrepreneurs. A total of 213 entrepreneurs comprising 106 Malays and 97 Chinese were surveyed using Pisapia’s strategic thinking measuring instrument. The instrument measures strategic thinking using three dimensions, reframing, reflection and systems thinking. The Malaysian entrepreneurs scored quite high on all three dimensions except for reframing. The scores on reframing of the Malays were found to be significantly lower than the Chinese entrepreneurs. This might explain why Chinese entrepreneurs are controlling the businesses in Malaysia. It is suggested that the government focus their training modules on this aspect of strategic thinking to further strengthen the competitiveness of our Malaysian entrepreneurs.